Thermo and photochromic properties of Na2O-WO3-SbPO4 glasses - Fernandes, N. I. [UNESP]; Poirier, G.; Nalin, M. (Elsevier B.V., 2010)
Tungsten phosphoantimoniate-based glasses containing sodium oxide were prepared and their thermochromic and photochromic properties investigated. Thermochromism is achieved by annealing glass samples at a temperature above glass transition (Tg). The phenomenon is characterized by an absorption band in the visible range and is non-reversible. These glasses also present photochromic properties when exposed to a laser beam (lambda = 457 nm) and this effect is characterized by a large absorption band extending from the near infrared to the visible range. Photochromism is reversible by heat treatment at 150 degrees C. The properties of these glasses, as well as colour changes were studied using differential scanning calorimetry, infrared, Raman, UV-vis and M-Lines spectroscopies, and X-ray diffraction. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Glasses; Tungsten; Thermochromism; Photochromism